Students’ Speaking Assessment Used by English Teachers Based on the 2013 Curriculum - Jannah, Waritsatul; Hartono, Rudi (English Education Journal, 2018)
The present study was focused on the speaking assessment used by some English teachers in Margasari sub-district. The objectives of this study are to explain; 1) the Implementation of Speaking Assessment based on 2013 Curriculum, 2) the types of speaking assessment used by English teachers, 3) teachers’ perception on speaking assessment based on 2013 curriculum, and 4) teachers’ perception of speaking assessment based on 2013 compared to school based curriculum. This research was qualitative. The data were collected by implementing interview and questionnaires, observation, and document analysis. The samples of this study were eight English teachers who taught seventh grade in some schools in Margasari sub-district by using purposive sampling technique. The data of this study were classified and analyzed qualitatively. The result of the study showed that; 1) the English teachers of some Junior High Schools in Margasari sub-district have implemented the speaking assessment, yet it was not properly conducted and did not fulfil the standard 2) the usage of performance based assessment was used in assessing the students’ speaking skill with role play as its most frequently implemented assessing activity, 3) the teachers’ perception towards the speaking assessment was very good, considered the problems that could be addressed and the solutions to overcome them, and 4) most of teachers’ perceived that speaking assessment based on 2013 curriculum and school based curriculum is different from several points of view yet the same on the activity of speaking test.